Implementasi Kurikulum Merdeka Belajar Dalam Menstimulasi Kecerdasan Musikal Anak Usia Dini - Ida Ayu Made Yuni Andari; Ida Bagus Alit Arta Wiguna (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
The kurikulum merdeka belajar emphasises learning that focuses not only on academic knowledge, but also on skills and attitudes. It equips learners with skills that are relevant to the evolving needs of the world of work. Musical intelligence involves the ability to appreciate, understand and make music. Children with this intelligence have sensitivity to rhythm, tone, and melody, and are able to express themselves through music. researchers are interested in examining more deeply the implementation of the kurikulum merdeka belajar in stimulating early childhood musical intelligence. This research uses descriptive qualitative research methods with a literature review research approach. data taken from various sources of written materials and then identifying contextual evidence by looking for relationships between data and the reality that the author examines. Some ways that can be used to stimulate and develop children's musical intelligence are: Musical exploration, Singing and singing together, Movement and dance, Making music and simple instruments, Musical performances, Integrating music in learning. Musical intelligence involves a person's ability to appreciate, understand, produce and express music. Individuals with strong musical intelligence are more sensitive to musical elements such as rhythm, pitch, harmony and expression. Media and tools to stimulate musical intelligence such as: Music recordings, Percussion instruments, Rhythmic instruments, Melodic instruments, Music apps and software, Musical books and stories, Group musical activities. Games that can stimulate and develop children's musical intelligence include listening games, imitation games, sound management games, song and movement games, composition games, sound teasers, guess the song games. The implications of the kurikulum merdeka belajar for stimulating children's musical intelligence are the development of musical skills, the development of auditory skills, the experience of harmony and well-being, the improvement of motor skills, the improvement of creativity, the improvement of cognition and concentration, the improvement of social and emotional skills. The constraints in stimulating early childhood musical intelligence are Limited resources, Lack of musical knowledge or skills, Limited time, Low interest or motivation of children, Differences in abilities and interests, Lack of environmental support.